Activity of predators in seabird colonies decreases during the darkest compared to the brightest phase of the diel cycle below, but not above, the Arctic Circle - Nicholas P. Huffeldt; Floris M. van Beest; Haley L. Kenyon; Jóhannis Danielsen; Tim Guilford (Arctic, Antarctic, and Alpine Research)
Predator activity can structure communities temporally and influence the spatial distribution of prey. Yet, despite the influence this may have on prey species’ activity or geographic persistence, our understanding of whether diel predator activity changes geographically remains limited. Here, we conduct a case study to test whether predator activity during the darkest phase of the diel cycle increases with the duration of daylight (i.e. photoperiod) at high latitudes during summer, aligning with the photoperiod constraint hypothesis. Using both observations and experiments at one seabird colony above and one below the northern polar (Arctic) circle, we compared predator activity between the brightest and darkest phases of the diel cycle. Avian predator counts were greater and nest predation events were more common during the brightest phase of the diel cycle below the Arctic Circle (i.e. where the sun goes below the horizon) but similar across phases during polar summer (i.e. above the Arctic Circle when the sun does not set). Our results highlight the potential influence of light on activity of predator communities and suggest a possible latitudinal limit to the advantage gained by dark-active strategies for avoidance of visually hunting predators.